10.已知下列热化学方程式 (1)CH3COOH(l)+2O2(g) 2CO2(g)+2H2O(1)△H1=-870.3kJ·mol-1 +O2(g) CO2(g)△H2=-393.5kJ·mol-1 (3)H2(g)+O2(g) H2O(1)△H3=-285.8kJ·mo-1. 2,4,6 则反应2C(s)+2H2(g)+O2(g) CH3COOH(1)的焓变△H为 ( ) A.488.3 kJ·mol-1 B.-244.15 kJ·mol-1 C.244.15kJ·mol-1 D.-488.3kJ·mol-1 查看更多

 

题目列表(包括答案和解析)

已知下列热化学方程式:

(1)CH3COOH(l) + 2O2(g) == 2CO2(g) + 2H2O(l)   △H1= -870.3 kJ·mol1

(2)C(s) + O2(g) == CO2(g)   △H2= -393.5 kJ·mol1

(3)H2(g) + 1/2 O2(g) == H2O(l)   △H3= -285.8kJ·mol1

 则反应:2C(s) + 2H2(g) + O2(g) == CH3COOH(l)的反应热为(   )

A.-488.3 kJ·mol1 B.-244.15 kJ·mol1 C.+488.3 kJ·mol1D.+244.15 kJ·mol1

 

查看答案和解析>>

已知下列热化学方程式:

(1)CH3COOH(l)+2O2(g) == 2CO2(g)+2H2O(l)  ΔH1=-870.3 kJ·mol-1

(2)C(s)+ O2(g) == CO2(g)  △H2=-393.5 kJ•mol-1

(3)H2(g) +O2(g) == H2O(l)  △H3=-285.8kJ·mol-1

则反应2C(s)+2H2(g) +O2(g) == CH3COOH(l)的△H为(    )

A.-488.3 kJ·mol-1    B.-244.15 kJ·mol-1    C.+488.3 kJ·mol-1  D.+244.15 kJ·mol-1

 

查看答案和解析>>

已知下列热化学方程式:

(1)CH3COOH(l)+2O2(g) == 2CO2(g)+2H2O(l)  ΔH1=-870.3 kJ·mol-1

(2)C(s)+ O2(g) == CO2(g)  △H2=-393.5 kJ•mol-1

(3)H2(g) +O2(g) == H2O(l)  △H3=-285.8kJ·mol-1

则反应2 C(s)+2H2(g) +O2(g) == CH3COOH(l)的△H为(    )

A. -488.3 kJ·mol-1 B.-244.15 kJ·mol-1  C.+488.3 kJ·mol-1 D.+244.15 kJ·mol-1

 

查看答案和解析>>

已知下列热化学方程式:

(1)CH3COOH(l)+2O2(g)===2CO2(g)+2H2O(l) ΔH1=-870.3 kJ/mol

(2)C(s)+O2(g)===CO2(g) ΔH2=-393.5 kJ/mol

(3)2H2(g)+O2(g)===2H2O(l) ΔH3=-571.6 kJ/mol

则反应2C(s)+2H2(g)+O2(g)===CH3COOH(l)的焓变为

A、-488.3 kJ/mol         B、-244.15 kJ/mol  C、488.3 kJ/mol          D、244.15 kJ/mol

 

查看答案和解析>>

已知下列热化学方程式:

(1)CH3COOH (l)+2O2 (g) == 2CO2 (g)+2H2O (l)  ΔH1=-870.3 kJ·mol-1

(2)C (s)+ O2 (g) == CO2 (g)  △H2=-393.5 kJ•mol-1

(3)H2 (g) +O2 (g) == H2O (l)  △H3=-285.8kJ·mol-1

则反应2C (s)+2H2 (g) +O(g) == CH3COOH (l)的△H为

A. -488.3 kJ·mol-1   B.-244.15 kJ·mol-1    C.+488.3 kJ·mol-1   D.+244.15 kJ·mol-1

 

查看答案和解析>>


同步练习册答案